“MENINA BONITA DO LAÇO DE FITA”: AS INTERFACES ENTRE CORPO, CULTURA E O SER NEGRO (A) NO AMBIENTE ESCOLAR - Carlos Barbosa dos Santos, Antônio; Neres Barbosa, Jonas; Aparecida Abade Santana, Maria; Batista Nunes, Ranchimit (Revista Form@re - Parfor/UFPI, 2026)
.